Meningkatkan Pemahaman Self-Compassion untuk Mengatasi Prokrastinasi Akademik pada Siswa SMP di Kabupaten Cirebon: Enhancing Understanding of Self-Compassion to Address Academic Procrastination among Junior High School Students in Cirebon Regency - Savira, Julia; Fahmi, Abu Bakar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
One of the obstacles in the learning process that students often face is the desire to procrastinate. This condition has the potential to make students feel self-guilt, regret, and excessive self-deprecation for neglecting their duties. In response to this, efforts are needed to increase students' understanding of academic procrastination and the importance of fostering self-compassion in themselves, one of which is by conducting psychoeducation. Psychoeducation activities are carried out in three stages, namely the planning, implementation, and evaluation stages of the activity. The participants in this activity were students of class IX-A at SMPN 2 Lemahabang, Cirebon Regency. This activity uses a questionnaire containing the same questions for the pre-test and post-test to measure participants' understanding before and after the activity. Analysis of the pre-test and post-test results showed that students experienced an increase in understanding after being given psychoeducation. Qualitatively, students also seemed enthusiastic and focused on the material presented. Thus, it can be concluded that the psychoeducation activities on academic procrastination and self-compassion have achieved the objectives set.